The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species - Cui, Yanze; Wang, Jun (Zootaxa, 2019)
A key to, and distributional information about, is given concerning the 11 Anaphothrips species known from China, including the descriptions of three new species: A. nonporous sp. n., A. oroqeni sp. n. and A. qinghaiensis sp. n. The male and micropterous female of A. beijing Mirab-balou, Chen & Tong and the male of A. populi Zhang & Tong are described for the first time. The European species A. atroapterus Priesner is newly recorded from China.